Kendala orang tua dalam mendampingi siswa ditinjau dari hasil belajar matematika secara online - Riri Puspita Dewi Permatasari; Ekasatya Aldila Afriansyah (Institut Pendidikan Indonesia, 2022)
Students' mathematics learning outcomes through online learning are still included in the poor category. In the current condition, parents have many obstacles in assisting students in learning mathematics online. The obstacles experienced by parents in assisting students to study at home include a lack of understanding of the material by parents. The purpose of this study was to analyze the constraints of parents in assisting students in terms of online mathematics learning outcomes. This research was conducted in Paas Village, Pameungpeuk District, Garut Regency. This study used a qualitative descriptive study with 5 students of class VII junior high school, 5 parents of class VII junior high school students, and 1 junior high school mathematics teacher of class VII, the selection of subjects was taken based on the level of parental education and parental occupation. The data collection technique used is triangulation (interviews, open questionnaires, and documentation). Data analysis techniques used are data reduction, data presentation, and data verification. The results of this study indicate that the more obstacles parents have in assisting students to learn mathematics online, the smaller the value of students' online mathematics learning outcomes. Obstacles of parents in accompanying students are most commonly found in the indicator of the educational background of parents with an average of 46% and the obstacles of parents in accompanying students are the least found in the indicator of the number of family members with an average of 30%. Hasil belajar matematika siswa melalui pembelajaran online masih termasuk dalam kategori kurang. Pada kondisi saat ini orang tua memiliki banyak kendala dalam mendampingi siswa dalam pembelajaran matematika secara online. Kendala-kendala yang dialami orang tua dalam mendampingi siswa belajar dirumah salah satunya meliputi kurangnya pemahaman materi oleh orang tua. Tujuan dari penelitian ini adalah untuk menganalisis kendala orang tua dalam mendampingi siswa ditinjau dari hasil belajar matematika secara online. Penelitian ini dilakukan di Desa Paas Kecamatan Pameungpeuk Kabupaten Garut. Penelitian ini menggunakan deskriptif kualitatif dengan subjek penelitian 5 siswa SMP kelas VII, 5 orang tua siswa SMP kelas VII, dan 1 guru matematika SMP kelas VII, pemilihan subjek diambil berdasarkan tingkat pendidikan orang tua dan pekerjaan orang tua. Teknik pengumpulan data digunakan secara triangulasi (wawancara, angket terbuka, dan dokumentasi). Teknik analisis data yang digunakan yaitu reduksi data, penyajian data dan verifikasi data. Hasil penelitian ini menunjukkan bahwa semakin banyak kendala orang tua dalam mendampingi siswa belajar matematika secara online, maka semakin kecil nilai hasil belajar matematika siswa secara online. Kendala orang tua dalam mendampingi siswa yang paling banyak ditemui pada indikator latar belakang pendidikan orang tua dengan rata-rata 46% dan kendala orang tua dalam mendampingi siswa yang paling sedikit ditemui pada indikator jumlah anggota keluarga dengan rata-rata 30%.